ANALISIS MANAJEMEN RANTAI PASOK PADA HOME INDUSTRY GETHUK PRESIDEN DI SRAGEN - In Nada Dwi Astriani; Erni Widajanti; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the optimization of supply chain management performance in the Gethuk President home industry in Sragen and to analyze the optimization of the impact of supply chain management performance on the Gethuk President home industry in Sragen. This type of research uses descriptive qualitative case study method. Data collection techniques used observation and interviews. The data analysis technique used descriptive supply chain analysis. The results showed that the supply chain management of gethuk products at the Presidential Gethuk Home Industry involved cassava farmers, collectors, Gethuk President and consumers. The supply chain structure is already running well. Chain management is running pretty well. The resource chain elements are already running well, starting from human resources, technology resources and capital resources. Chain business process elements are elements that are considered optimal because smooth production and marketing are already very good.